2015
DOI: 10.1080/15592294.2015.1061174
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic landscape correlates with genetic subtype but does not predict outcome in childhood acute lymphoblastic leukemia

Abstract: Although children with acute lymphoblastic leukemia (ALL) generally have a good outcome, some patients do relapse and survival following relapse is poor. Altered DNA methylation is highly prevalent in ALL and raises the possibility that DNA methylation-based biomarkers could predict patient outcome. In this study, genome-wide methylation analysis, using the Illumina Infinium HumanMethylation450 BeadChip platform, was carried out on 52 diagnostic patient samples from 4 genetic subtypes [ETV6-RUNX1, high hyperdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…In addition, we also took 15 surrogate variables into account—a procedure which has been demonstrated to address latent subjects which may affect DNAm [59]. We did not attempt to replicate the DNAm measurements based on the Illumina 450 K array with other methods such as pyrosequencing since this array has been shown to be technically reliable in multiple studies [60,61,62,63,64,65,66,67]. Another limitation of this study is that blood subsets could not be collected in all three trimesters; however, the separation of gestation into trimesters is arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also took 15 surrogate variables into account—a procedure which has been demonstrated to address latent subjects which may affect DNAm [59]. We did not attempt to replicate the DNAm measurements based on the Illumina 450 K array with other methods such as pyrosequencing since this array has been shown to be technically reliable in multiple studies [60,61,62,63,64,65,66,67]. Another limitation of this study is that blood subsets could not be collected in all three trimesters; however, the separation of gestation into trimesters is arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of these abnormalities not only reveals underlying molecular pathology, but also provides important therapeutic targets, as exemplified by the improved outcome achieved with ABL tyrosine kinase inhibitors in patients with Philadelphia chromosome-positive or Philadelphia chromosome-like ALL patients with ABL class fusion transcripts ( Schultz et al, 2014 , Chalandon et al, 2015 , Roberts et al, 2014 ). Recent technologic advances have enabled detailed characterization of the genomic landscape of childhood ALL, including DNA sequence abnormalities such as single nucleotide variations (SNV), small insertions or deletions (indels) and copy number variations (CNV) ( Mullighan et al, 2007 ); gene expression anomalies ( Roberts et al, 2014 , Den Boer et al, 2009 ); gene fusions due to cryptic chromosomal rearrangements ( Roberts et al, 2014 , Gocho et al, 2015 ); and aberrant epigenetic modifications including abnormal DNA methylation, histone modifications and mutations of epigenetic modifier genes ( Gabriel et al, 2015 ). The precise contribution of these genetic or epigenetic abnormalities to leukemogenesis, the development of drug resistance and leukemic clone evolution remains to be defined ( Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of other studies have revealed that the spectrum of genes with potentially aberrated methylation in BCP ALL is very wide and includes many biological processes. These processes include, among others, growth and proliferation’s regulation [ 26 , 29 – 31 ], apoptosis [ 26 , 29 , 30 , 37 ] hematopoiesis and lymphocyte B development [ 27 , 28 , 36 ] and immune response [ 38 ]. It must be noted that alteration of promoter DNA methylation does not have to translate to major changes in gene expression in any case [ 26 ].…”
Section: Discussionmentioning
confidence: 99%